Advances in model-based software testing (A-MOST). - Dalal, Siddhartha R. (Software engineering notes.)
This is a summary of the Advances in Model-Based Software Testing (A-MOST) workshop held on May 15-16, 2005, in St. Louis, Missouri. The workshop had approximately 40 participants. The goals of this workshop were to offer a comprehensive overview of model-based testing to the ICSE community, and bring the researchers and practitioners together to discuss advances, applications, and the complex problems yet to be solved in model-based testing. The workshop was lively and maintained participant interest for the entire two-day program. A brief summary based upon agenda items is provided. Details on the workshops are archived at http://aetgweb.argreenhouse.com.